Arl4D-EB1 interaction promotes centrosomal recruitment of EB1 and microtubule growth - Lin, Shin-Jin; Huang, Chun-Fang; Wu, Tsung-Sheng; Li, Chun-Chun; Lee, Fang-Jen S. (Molecular biology of the cell, 2020)
The GTP-bound form of ADP-ribosylation factor-like 4D (Arl4D) small GTPase localizes to the centrosome and interacts with microtubule (MT) end-binding 1 (EB1) protein. Arl4D-EB1 interaction promotes EB1 centrosomal recruitment and increases the association of EB1 and p150 subunit of dynactin, thereby contributing to the nucleation of MTs at the centrosome. ADP-ribosylation factor (Arf)-like 4D (Arl4D), one of the Arf-like small GTPases, functions in the regulation of cell morphology, cell migration, and actin cytoskeleton remodeling. End-binding 1 (EB1) is a microtubule (MT) plus-end tracking protein that preferentially localizes at the tips of the plus ends of growing MTs and at the centrosome. EB1 depletion results in many centrosome-related defects. Here, we report that Arl4D promotes the recruitment of EB1 to the centrosome and regulates MT nucleation. We first showed that Arl4D interacts with EB1 in a GTP-dependent manner. This interaction is dependent on the C-terminal EB homology region of EB1 and partially dependent on an SxLP motif of Arl4D. We found that Arl4D colocalized with γ-tubulin in centrosomes and the depletion of Arl4D resulted in a centrosomal MT nucleation defect. We further demonstrated that abolishing Arl4D-EB1 interaction decreased MT nucleation rate and diminished the centrosomal recruitment of EB1 without affecting MT growth rate. In addition, Arl4D binding to EB1 increased the association between the p150 subunit of dynactin and the EB1, which is important for MT stabilization. Together, our results indicate that Arl4D modulates MT nucleation through regulation of the EB1–p150 association at the centrosome.